A Multimodal Multi‐Shank Fluorescence Neural Probe for Cell‐Type‐Specific Electrophysiology in Multiple Regions across a Neural Circuit. Issue 2 (19th November 2021) - Chou, Namsun; Shin, Hyogeun; Kim, Kanghwan; Chae, Uikyu; Jang, Minsu; Jeong, Ui‐Jin; Hwang, Kyeong‐Seob; Yi, Bumjun; Lee, Seung Eun; Woo, Jiwan; Cho, Yakdol; Lee, Changhyuk; et al.
Abstract: Cell‐type‐specific, activity‐dependent electrophysiology can allow in‐depth analysis of functional connectivity inside complex neural circuits composed of various cell types. To date, optics‐based fluorescence recording devices enable monitoring cell‐type‐specific activities. However, the monitoring is typically limited to a single brain region, and the temporal resolution is significantly low. Herein, a multimodal multi‐shank fluorescence neural probe that allows cell‐type‐specific electrophysiology from multiple deep‐brain regions at a high spatiotemporal resolution is presented. A photodiode and an electrode‐array pair are monolithically integrated on each tip of a minimal‐form‐factor silicon device. Both fluorescence and electrical signals are successfully measured simultaneously in GCaMP6f expressing mice, and the cell type from sorted neural spikes is identified. The probe's capability of combined electro‐optical recordings for cell‐type‐specific electrophysiology at multiple brain regions within a neural circuit is demonstrated. The new experimental paradigm to enable the precise investigation of functional connectivity inside and across complex neural circuits composed of various cell types is expected. Abstract : A multimodal multi‐shank fluorescence neural probe allows cell‐type‐specific electrophysiology from multiple deep‐brain regions at a high spatiotemporal resolution. The tip of probe monolithically integrates photodiode and an electrode‐array pair to measure both fluorescence and electrical signals simultaneously. The probe enables combined electro‐optical recordings for cell‐type‐specific electrophysiology at multiple brain regions within a neural circuit.